Strategi Dan Penanggulangan Tindakan Perundungan Siber Di Sosial Media - Sri Tari Utami (Institute of Information Technology and Social Science (IITSS), 2022)
The development of information technology and internet penetration has brought about significant changes in social interaction patterns, with social media becoming the main platform for bold interactions. However, the phenomenon of cyberbullying on social media is becoming an increasingly deep and disturbing issue that continues to have a negative impact on the individuals involved. The Indonesian government has responded seriously to this problem by launching various initiatives, including social media awareness campaigns, to prevent and reduce cyberbullying. This research aims to investigate in depth strategies and countermeasures for cyberbullying on social media. The phenomenon of cyber bullying is not only influenced by internal individual factors, but also by external factors such as the environment, technology and social organizations. In this context, this research will analyze the impact of these factors and formulate effective prevention strategies using a literature review method to analyze a number of aspects that are closely related to bullying on social media to build a deep understanding of good behavior in the digital world. . . With this understanding, Indonesia is expected to be able to reflect the values and norms that apply in maintaining a safe and inclusive digital environment. The research results show that internal factors such as personal initiative and external factors such as the environment and technology play a role in triggering bullying on social media. Prevention can be done through improving ethical behavior on the internet, activating the role of parents, socialization and anti-bullying education activities by the police, and anti-bullying campaigns by social organizations.